Estimates of the air-fuel ratio at the time of ignition in a pre-chamber using a narrow throat geometry. (February 2023) - Hlaing, Ponnya; Silva, Mickael; Marquez, Manuel Echeverri; Cenker, Emre; Ben Houidi, Moez; Im, Hong G; Turner, James WG; Johansson, Bengt
The benefits of pre-chamber combustion (PCC), such as improved engine efficiency and reduced NOx emissions, are primarily observed when operating at lean conditions with an active pre-chamber, where auxiliary fuel is supplied directly to the pre-chamber. Estimating the pre-chamber excess air ratio (λ) is important in the active pre-chamber concept to gain insights into the pre-chamber combustion phenomenon. Experimental investigations were performed using a narrow-throat pre-chamber at global-λ 1.6, 1.8, and 2.0. The fraction of fuel energy injected in the pre-chamber over the total fuel energy was fixed at 3%, 7%, and 13% for each global-λ. The mixture formation process inside the pre-chamber is first simulated using the 1-D simulation software GT-Power to analyze the pre-chamber λ at the ignition timing. However, the 1-D results were unable to reproduce the experimental observations on the pre-chamber pressure buildup accurately. Upon simulating the same conditions using the 3-D CFD software CONVERGE, the pre-chamber λ estimated from the CFD model is well-correlated to the experimental data. The CFD results indicate that the amount of fuel trapped in the pre-chamber at the inlet valve closing timing is over-predicted by the 1-D simulations. A correlation between the injected and the trapped fuel in the pre-chamber is proposed by theoretical scavenging models and applied to the 1-D simulation results to improve pre-chamber λ prediction accuracy.